The nexus of energy resources and the environment - Bishoge, Obadia Kyetuza (Journal of Ecobiotechnology, 2021)
Currently, every country is striving to realize development for its people. Thus, to achieve this there is a need for ensuring access to reliable energy at all levels. The world is currently relying on the use of non-renewable energy such as fuels, and coal. However, these sources are not environmental friendly. Thus, renewable energy sources such as hydropower, solar energy, geothermal, and biofuels must be emphasized to replace the use of non-renewable energies. People need to understand well the relationship between energy resources and the environment. This paper, therefore, aims at providing the nexus of energy resources and the environment. To achieve this, the author has explained well the concept of energy and energy resources; energy uses and energy efficiency and energy security. Moreover, the author has discussed the impact of energy resources on the environment. Finally, energy savings and practices to best energy use; use of technologies to reduce the pollutant emissions in the atmosphere; and investment in renewable technologies are needed for attaining sustainable energy and environment.